1990
DOI: 10.1210/endo-127-3-1078
|View full text |Cite
|
Sign up to set email alerts
|

Transcapillary Permeability and Subendothelial Distribution of Endothelial and Amniotic Fluid Insulin- Like Growth Factor Binding Proteins in the Rat Heart*

Abstract: Insulin-like growth factor (IGF) binding proteins (IGFBP) were purified from conditioned media of cultured bovine endothelial cells (ECBP) and from human amniotic fluid (IGFBP-1), and then labeled by radioiodination. 125I-ECBP and 125I-IGFBP-1 were perfused through isolated beating rat hearts for 1 and 5 min, and the hearts fixed and analyzed for 125I-BP content and distribution. One to 4% of the perfused 125I-ECBP and 125I-IGFBP-1 crossed the capillary boundary. The ECBPs predominantly localized as intact 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(58 citation statements)
references
References 30 publications
2
56
0
Order By: Relevance
“…11 It also accelerates IGFBP-1 transport from the intravascular space through the endothelial walls of the capillaries to the target cells. 11,12 However, the associations between IGFBP-1 levels and BMI, WHR, and HDL cholesterol were independent of insulin levels. This observation suggests that a low IGFBP-1 level might be an independent marker for the metabolic disturbances, which are all associated with an increased risk of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 It also accelerates IGFBP-1 transport from the intravascular space through the endothelial walls of the capillaries to the target cells. 11,12 However, the associations between IGFBP-1 levels and BMI, WHR, and HDL cholesterol were independent of insulin levels. This observation suggests that a low IGFBP-1 level might be an independent marker for the metabolic disturbances, which are all associated with an increased risk of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 IGFBP-1, one of these IGFBPS, is not restricted to the circulation and is considered to function as a transport protein that shuttles IGF-I from the intravascular space through the endothelial walls of the capillaries. 11,12 IGFBP-1 has been proposed as an acute regulator of IGF-I bioactivity and might simultaneously both inhibit and potentiate IGF-I action at different sites. 13 Recent evidence even suggests that IGFBP-1 has intrinsic mitogenic and metabolic activity.…”
mentioning
confidence: 99%
“…This result is not surprising as binary IGFBP:IGF complexes are not restricted by endothelial barriers. In fact, IGFBPs may have a role in the specific targeting of IGFs to specific tissues (27)(28)(29). The organ distribution of 125 I-labelled IGFBP-3 (30) and IGFBP-6 were similar, with both IGFBPs being predominantly localised to the stomach and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The considerable developmental changes of IGFBPs in sheep perinatal time are influenced by IGF-I availability for its biological function. Bar et al (1990) found that bovine endothelial cell binding proteins (ECBP) and amniotic fluid IGFBP-1 are able to cross rat heart capillary vessels and ECBP are localized preferentially in myocardial connective tissues in comparison with IGFBP-1 which has higher affinity to the myocardium. IGF-I like IGFBP-1 is also leaving the vascular spaces and is distributed into heart muscle during the heart perfusion by this IGF.…”
Section: Carrier Functionmentioning
confidence: 99%